Analysis of Mechanical Properties of Shape Memory Alloy - Gözde KONUK EGE; Nihat AKKUS; Mucahit EGE (International Journal of Applied Methods in Electronics and Computers, 2016)
In this study, a particular mechanism is designed to obtain the mechanical properties of shape memory alloys (SMA). Mechanical behavior occurring due to the super elastic properties is investigated by applying current to shape memory alloys via designed mechanism. Displacement, velocity, time, force physical effects of SMA springs is obtained for different current values, and active operating range of springs is determined. This acquired data are of importance in determining the area of use of shape-memory alloys. This paper presents the structure of the designed mechanism and data of mechanical properties of shape memory alloys which are obtained by using this designed mechanism.